AMYANDS’ HERNIA IN A NEONATE – A RARE CLINICAL ENTITY - Muhammad Jamil; Muhammad Afzal; Rashid Usman (Journal of University Medical & Dental College, 2016)
ABSTRACT Amyand’s hernia occurs rarely where inguinal hernia sac contains normal or inflamed vermiform appendix. We are reporting a case of Amyands hernia in just a four weeks old child who presented with an irreducible swelling in right inguinoscrotal area. On exploration, appendix was found in the hernial sac. . Appendectomy and herniotomy were performed. Post op recovery was uneventful. To our best of our knowledge Amyands hernia in a neonateis being reported for the first time in any national journal